The Effectiveness of Project-Based Learning (PjBL) to Improve Motivation on the 8th Students’ Writing Skill of Narrative Text at SMPN-1 Murung - Beny Endriyanto; Ristati, Ristati; Misrita, Misrita (Journal Pendidikan Ilmu Pengetahuan Sosial, 2023)
Writing is one of the skills students need to write different types of writing. However, not all students have good enough writing skills to use this at school. The problem was identified by the researcher in his previous observations of an SMPN-1 Murung, specifically in 8th grade, on March 9, 2023. Student tasks consist of choosing appropriate words, using grammar (simple past tense), developing ideas, and using punctuation marks. A student's average score is below 60 on the KKM (Kriteria Ketuntasan Minimal), but her KKM at the school is expected to be 72. Based on this issue, the researcher applied the project-based learning (PjBL) model to help students improve their writing skills in the classroom. The technique for collecting samples is purposive sampling, and the technique for determining control and experimental groups is odd-even technique. The type of this study is a quasi-experimental with pre-test, treatment (using the PjBL method), and post-test design. The sample consists of 48 students of 8th grade from SMPN-1 Murung. Data collection techniques include pre-tests and post-tests. SPSS version 21 was used for data analysis. Based on data analysis, the experimental group had a mean pre-test score of 59.5 and a mean post-test score of 75.75. Finally, based on hypothesis testing, the significance value is 0.000 < 0.05 (sign value lower than t table). From this, we can conclude that Ha (the alternative hypothesis) is accepted and H0 (the null hypothesis) is rejected. Based on the results of this study, English teacher can be recommended using PjBL when teaching narrative text of writing to the 8th students of SMPN-1 Murung